Thermal properties of matter - Khachan, Joe (Morgan & Claypool Publishers, 2018)
The ancient Greeks believed that all matter was composed of four elements: earth, water, air, and fire. By a remarkable coincidence (or perhaps not), today we know that there are four states of matter: solids (e.g. earth), liquids (e.g. water), gasses (e.g. air) and plasma (e.g. ionized gas produced by fire). The plasma state is beyond the scope of this book and we will only look at the first three states. Although on the microscopic level all matter is made from atoms or molecules, everyday experience tells us that the three states have very different properties. The aim of this book is to examine some of these properties and the underlying physics.
"A Morgan & Claypool publication as part of IOP Concise Physics"--Title page verso.
Keywords: Thermodynamics.; Physics.; SCIENCE / Physics / General.; elektronické knihy; electronic books